Pengaruh Media Pembelajaran Terhadap Hasil Belajar Keterampilan Gerak Senam Lantai Guling Ke Depan Pada Peserta Didik SMP Negeri 2 Tondano - Claudia Stien Mawu; Yuliana Sattu; Djajaty M. Lolowang (STIKES Columbia Asia Medan, 2025)
This study examines the impact of learning media on the learning outcomes of floor gymnastics, specifically the forward roll, among students at SMP Negeri 2 Tondano. The research aimed to determine whether audiovisual learning media could improve students’ performance in performing the forward roll. The study employed an experimental design with a randomized control group pre-test and post-test. The sample consisted of 26 students, divided into an experimental group that received media-based learning and a control group. Data were collected using a pre-test and post-test measuring students' gymnastics skills. The results indicate that the experimental group showed a significant improvement in their skills compared to the control group. This suggests that audiovisual media enhances students' understanding and performance of complex movements in gymnastics. The implications of this study are significant for physical education teachers, emphasizing the importance of using innovative learning media to increase student engagement and skill acquisition. Further research is recommended with larger sample sizes and considering additional learning tools.